Pengolahan Limbah Domestik Dengan Kolam Sanitasi Secara Komunal - Chayati, Cholilul Chayati; Ahmad Suwandi (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2022)
Marengan Laok village is a village in Kalianget sub-district which is one of the sub-districts in Sumenep Regency. Marengan Laok village is a village located on the coast and is one of the salt-producing villages and a village with a densely populated category with a number of household’s ± 1,436 there are 4 Hamlets (Jennengan, Beddi, Jenengan, and Mosque). Based on the identification of the problem, and considering that the village of Marengan Laok is a dense settlement, the aim of the study is to plan for sewage treatment with communal sanitation ponds. For planning for communal processing, it is planned to use unproductive salt ponds in Jenengan hamlet. According to Law Number 18 of 2008, domestic waste is waste that comes from daily activities in the household but does not include feces. Daily activities that can produce waste are washing, cooking, bathing, agricultural activities, and livestock activities. The 2020 population of 669 people is projected in 2025 as many as 735 people with the potential for waste generated by 120 l/day septic tanks are planned to accommodate 50 users, the total number of septic tanks needed is 15 units with a storage volume of 18.63 m³/piece, the volume of the sanitation pond is 6 m the types of plants used for the sanitation pond of kana flower and jasmine water. Waste management planning with a sanitary pond based on SNI 2398:2017